Pengaruh Struktur Modal, Profitabilitas Dan Growth Opportunity Terhadap Nilai Perusahaan ( Studi Empiris Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Kusumaningrum, Santy; , Dr. Syamsudin, M.M (2017)
This research aims to analyze the effect of capital structure, profitability and Growth Opportunity Of the company are measured using a price book value, on food and beverage companies listed on the Indonesia stock exchange in 2012- 2015. The population used in this study are food and beverage companies listed on the Indonesia stock exchange in 2012-2015. Sampling method sampling purposive manner in accordance with the criteria specified. The number of samples collected as many as 14 companies. Research data is secondary data obtained from the Indonesian Capital Market Directory (ICMD) in 2012-2014 and the data provided on the website of the indonesia stock exchange (www.idx.go.id) by 2015. Data that has been collected is analyzed by using the data analysis done first before doing the classic assumption test hypothesis testing. Hypothesis testing in this study using multiple linear regression analysis with t test, f test and a test of the determination of the coefficients using the SPSS program. The results showed that simultaneously throughout the independent variable structure of capital, profitability and growth opportunity in this research the positive and significant effect against the value of the company's food and beverage companies listed on the Indonesia stock exchange in 2012-2015. Companies need to pay attention to the structure of capital, profitability and growth opportunity that when increasing the third variable occurs then investors will be attracted to the company by investing capital.